Sporicidal and antibacterial effect of sterilization of dental-surgical instruments - Bautista, Charlie Sibayan (San Carlos City, Pangasinan : [s.n.], 2005)
This study was conducted to provide further understanding and interest to the dental clinicians on the sterilization methods so that these can be incorporated in the Surgery Infirmary of the College of Dentistry, Virgen Milagrosa University Foundation and further apply such methods in thier future dental practice.
Bibliography: pages 101-103
CHED-La Union
Keywords: Dental care